Half-metallicity in new Heusler alloys Mn2ScZ (Z = Si, Ge, Sn). Issue 13 (21st February 2020) - Ram, Mahesh; Saxena, Atul; Aly, Abeer E.; Shankar, Amit
Abstract : Study of half-metallicity has been performed in a new series of Mn2 ScZ (Z = Si, Ge and Sn) full Heusler alloys using density functional theory with the calculation and implementation of a Hubbard correction term ( U ). Abstract : Study of half-metallicity has been performed in a new series of Mn2 ScZ (Z = Si, Ge and Sn) full Heusler alloys using density functional theory with the calculation and implementation of a Hubbard correction term ( U ). Volume optimization in magnetic and non-magnetic phases for both the Cu2 MnAl and Hg2 CuTi type structures was done to predict the stable ground state configuration. The stability was determined by calculating their formation energy as well as from elastic constants under ambient conditions. A half-metal is predicted for Mn2 ScSi and Mn2 ScGe with a narrow band gap in the minority spin whereas Mn2 ScSn shows a metallic nature. The magnetic moments of Mn and Sc are coupled in opposite directions with different strengths indicating that the ferrimagnetic order and the total magnetic moment per formula unit for half-metals follows the Slater Pauling rule. And a strong effect was shown by the size of the Z element in the electronic and magnetic properties.